SARS-COV-2 human monoclonal antibody therapy update - Crowe, James (Henry Stewart Talks, 2021)
Review of the research done since the start of the pandemic, Current work covering the SARS-CoV-2 variants, The selection process of monoclonal antibodies for development, Next steps in the research and future strategies, The AHEAD100 project i.e. generating neutralizing antibodies for the 100 most likely causes of future epidemics